The Influence of Local Government Financial Factors on the 2021 Budget Forecast Error: Studies on Local Governments in Indonesia - Yohana Febiani Angi; Minarni A. Dethan; , Maria Indriyani H. Tiwu (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
The APBD aims to coordinate financing within local government and create transparency in local government budgets. The components of the APBD consist of regional income, regional spending and budget financing . In the process of preparing the APBD, the structure and contents of the APBD are adjusted to the needs of government administration and regional government revenues within one fiscal year. This type of research uses a quantitative approach with a research design of hypothesis testing studies . In sample research, this research uses purposive sampling with the aim of obtaining a representative sample according to the criteria, namely the Provincial Government which has the highest SILPA in 2021. The dependent variable Budget Forecast Errors has an average of 1.39 and a maximum value of 9.45. The minimum value is 0.91 and the standard deviation value is 1.79. These results can be explained that the Regional Original Income variable has a high average value when compared to the standard deviation, which is 103.74 greater than 12.84. The independent variable Balancing Fund has an average value of 100.62, a maximum value of 106.85, a minimum value of 95.66, and a standard deviation value of 3.26. These results can be explained that the average value of the Other Legal Regional Income variables is relatively high when compared to the standard deviation, which is 114.74 greater than 43.78. The independent variable Direct Spending has an average value of 91.21, a maximum value of 115.34, a minimum value of 58.88, and a standard deviation value of 13.42.